Assessment of the cyclical nature of fiscal policy in the EAEU countries - S. E. Demidova (Модернизация, инновация, развитие, 2025)
Purpose: is to assess the cyclical nature of fiscal policy through the analysis of government debt, budget expenditures and tax rates on individual taxes for a group of countries belonging to the Eurasian Economic Union.Methods: the methodological basis of the study was the concept of fiscal space, a systematic approach, and dynamic analysis. Regression analysis was performed using the least squares method on panel data. To assess the cyclical nature of fiscal policy, the fiscal variables are the growth rates of government spending and tax rates, the growth rate of real GDP serves as a measure of economic activity. The methods of economic and statistical analysis, scientific abstraction, analogies, scientific generalizations, and expert assessments were used.Results: in the EAEU countries, a weak influence of the public debt level on economic growth has been revealed. The countercyclical nature of budget expenditures and tax rates has been confirmed over the considered time horizon, although most scientific papers confirm the procyclical nature of fiscal policy in emerging economies. The study showed that countries are fiscally countercyclical in terms of valueadded tax, corporate income tax, and personal income tax. The presented models on value-added tax show a very weak countercyclical nature.Conclusions and Relevance: the estimates obtained indicate that, in general, the conclusion regarding the countercyclical nature of fiscal policy in the EAEU countries during the period under review, including regarding value added tax, is supported. The latter is primarily characterized by an acyclic pattern. One reason for this may be the nature and specifics of fiscal regulations. The level of public debt has only a minor impact on the dynamics of economic growth in this group of countries, due to its low volume and moderate growth. At the same time, institutional factors play a significant role. The results obtained can be used both in further studies of fiscal policy issues and in making policy decisions, especially in the context of forecasts of a long-term increase in debt and the need to increase government spending.